UPAYA MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA KRISTEN SISWA MELALUI MODEL PEMBELAJARAN PICTURE AND PICTURE DI KELAS IX-J SMPN 1 SIDIKALANG - Helmi Rohani Purba (Universitas Negeri Medan, 2018)
Abstract : Effort Increasing Result Of Educational Religious Christ Education Through Learning Model Picture And Picture In Class IX-J SMPN 1 Sidikalang. This study aims to improve learning activities and student learning outcomes that include student learning activities while working in class groups in Christian subjects that leads to increased activity and student learning outcomes by applying the model of learning Picture and Picture. The subjects of this study were taken in class IX-J SMP Negeri 1 Sidikalang with the number of students 34 people. Based on the data obtained; 1) The results of student learning in class IX-J SMP Negeri 1 Sidikalang after the implementation of cooperative learning model Picture and Picture during learning Christian Religious Education, which is an increase in student learning outcomes from cycle I to cycle II both individually and classical. eased to 31 people who complete the individual and the class completely.Keywords: Model Picture and Picture Learning, Learning Activity Learning Outcomes.Abstrak : Upaya Meningkatkan Hasil Belajar Pendidikan Agama Kristen Siswa melalui Model Pembelajaran Picture And Picture di Kelas IX-J SMPN 1 Sidikalang. Penelitian ini bertujuan untuk meningkatkan aktivitas belajar dan hasil belajar siswa yang mencakup aktivitas belajar siswa saat bekerja dalam kelompok dikelas pada mata pelajaran Agama Kristen yang bermuara pada peningkatan aktivitas dan hasil belajar siswa dengan menerapkan model pembelajaran Picture And Picture. Subjek penelitian ini diambil di kelas IX-J SMP Negeri 1 Sidikalang dengan jumlah siswa 34 orang. Berdasarkan data yang diperoleh; 1) Hasil belajar siswa di kelas IX-J SMP Negeri 1 Sidikalang setelah diterapkannya model pembelajaran kooperatif Picture And Picture selama pembelajaran Pendidikan Agama Kristen, yaitu terjadi peningkatan hasil belajar siswa dari siklus I ke siklus II baik secara individu maupun klasikal.Kata Kunci : Model Pembelajaran Picture And Picture, Aktivitas Belajar Hasil Belajar.